Investigations of magnetic and dielectric properties of cupric oxide nanoparticles - Bhalerao-Panajkar, Rohini S.; Shirolkar, Mandar M.; Das, Raja; Maity, Tuhin; Poddar, Pankaj; Kulkarni, S. K. (Solid State Communications, 2011)
Cupric oxide nanoparticles of similar to 8-10 nm width and 40-45 nm length self assembled as large particles similar to 1-1 5 mu m have been investigated in the 10-325 K temperature range using magnetic and dielectric measurements In magnetic measurements a single broad peak at similar to 230 K in a zero field cooled sample has been observed Coercivity in magnetization measurements at 10 K suggests that the nanoparticles are core-shell type particles with an antiferromagnetic core and a ferromagnetic shell Dielectric measurements at various frequencies from 3 7 Hz to 949 kHz exhibit a sharp peak at 284 K followed by weak anomalies around 213 and 230 K (C) 2010 Elsevier Ltd All rights reserved
Keywords: CuO nanoparticles; Dielectric; Ferroelectric transition; Ferromagnetic

Interchain relay of antiferromagnetic ordering in 1D Co(II) coordination polymers via pi-pi interactions - Ahmad, Musheer; Das, Raja; Mrozinski, Jerzy; Bienko, Alina; Poddar, Pankaj; Bharadwaj, Parimal K. (CrystEngComm, 2014)

Ionic control on the morphology of ytterbium manganese oxide nanorods and nanoplates in a surfactant-free synthesis and their magnetic properties - Das, Raja; Poddar, Pankaj (Journal of Physical Chemistry C, 2014)
Here, we report the synthesis of multiferroic, single-crystalline ID YbMnO3 in nanoregime. By using ionic chemistry without the use of surfactant or template, we demonstrate control synthesis of one- and two-dimensional nanoparticles of YbMnO3. Magnetic properties of YbMnO3 show influence of morphology. Detailed alternating current (ac) and direct current (dc) magnetic study shows ferromagnetic interaction of Mn3+ and Yb3+ moments in nanorods of YbMnO3 below similar to 35 K.